2016
DOI: 10.1111/cmi.12549
|View full text |Cite
|
Sign up to set email alerts
|

TheChlamydia trachomatisCtad1 invasin exploits the human integrin β1 receptor for host cell entry

Abstract: Infection of human cells by the obligate intracellular bacterium Chlamydia trachomatis requires adhesion and internalization of the infectious elementary body (EB). This highly complex process is poorly understood. Here, we characterize Ctad1 (CT017) as a new adhesin and invasin from C. trachomatis serovar E. Recombinant Ctad1 (rCtad1) binds to human cells via two bacterial SH3 domains located in its N-terminal half. Pre-incubation of host cells with rCtad1 reduces subsequent adhesion and infectivity of bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 58 publications
1
47
0
Order By: Relevance
“…The level and position of sulfation in HSPGs have important roles in the binding of C. muridarum and C. trachomatis L2 (REFS 17,28,29) and may contribute to tissue tropism. Other adhesins include lipopolysaccharide (LPS) in C. trachomatis , which is proposed to bind to the cystic fibrosis transmembrane conductance regulator 17,30 , major outer membrane protein (MOMP; also known as CT681), which binds to the mannose receptor and the mannose 6-phosphate receptor 18 , and CT017 (also known as Ctad1) in C. trachomatis , which binds to β1 integrin 31 . The polymorphic membrane protein (Pmp) family in C. trachomatis and C. pneumoniae also mediates adhesion 32 .…”
Section: Binding and Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level and position of sulfation in HSPGs have important roles in the binding of C. muridarum and C. trachomatis L2 (REFS 17,28,29) and may contribute to tissue tropism. Other adhesins include lipopolysaccharide (LPS) in C. trachomatis , which is proposed to bind to the cystic fibrosis transmembrane conductance regulator 17,30 , major outer membrane protein (MOMP; also known as CT681), which binds to the mannose receptor and the mannose 6-phosphate receptor 18 , and CT017 (also known as Ctad1) in C. trachomatis , which binds to β1 integrin 31 . The polymorphic membrane protein (Pmp) family in C. trachomatis and C. pneumoniae also mediates adhesion 32 .…”
Section: Binding and Invasionmentioning
confidence: 99%
“…In addition to the β1 integrin subunit 31 and EGFR 33 , receptor tyrosine kinases (RTKs) contribute to binding, invasion and signalling during entry. C. trachomatis and C. muridarum interact with the fibroblast growth factor receptor (FGFR) and its ligand FGF as well as platelet derived growth factor receptor (PDGFR) 34,35 .…”
Section: Binding and Invasionmentioning
confidence: 99%
“…Much of our current understanding of the roles that specific chlamydial effectors and their interactive host partners play in these processes is derived from cell systems 58596061 and animal models 6263. Candidate receptors that promote chlamydial attachment to susceptible cells have been identified 646566. Not unsurprisingly for a microorganism that interacts with its host cell across the plasma membrane at attachment and entry and with the inclusion membrane during the remainder of the developmental cycle, secretion systems represent a significant portion of the chlamydial genome.…”
Section: Chlamydia Trachomatis - Genital Tract Pathogenmentioning
confidence: 99%
“…Recent studies have shown that two C. pneumoniae proteins, adhesin CPn0473 and invasin Pmp21, bind to host epidermal growth factor receptor (EGFR) and trigger lipid raft-mediated uptake (Mölleken et al, 2013; Fechtner et al, 2016). C. trachomatis also adhered to the lipid raft protein EphrinA2 receptor (EphA2) (Chakraborty et al, 2012; Subbarayal et al, 2015), and the C. trachomatis invasin protein Ctad1 bound to β1 integrin in lipid rafts during internalization (Stallmann and Hegemann, 2016). Targeting multiple host cell lipid raft receptors may broaden host cell tropism and increase the potential for successful host cell colonization.…”
Section: Role Of Cholesterol In Bacterial Entry and Exitmentioning
confidence: 99%